The Effect of Per Capita Expenditure on the Working Status of the Elderly in Indonesia - Amania, Atina Asyfa; Usman, Hardius (Populasi, 2024)
The increasing number of elderly people indicates that Indonesia has begun to enter the second demographic bonus. This stage can be beneficial if the elderly remain productive and contribute to development. One of the things closely related to the elderly population and remains the development capital is their work activity. In Indonesia, the percentage of elderly who work also continues to increase yearly. However, most of them have low per capita expenditure, indicating that their low welfare motivates the elderly to work. This research aims to study the general description and characteristics of the elderly and working elderly in Indonesia, examine the effect of per capita expenditure on their working status, and analyze the differences in the effect considering other variables. The data is sourced from the March 2023 National Socio-Economic Survey (NSES), and the study utilizes binary logistic regression with interaction effects. The results showed that per capita expenditure has a significant effect on the working status of the elderly, but the effect is different in terms of place of residence, age, gender, head of household status, marital status, education level, health complaint status, and ownership of health insurance.